PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION TAMU PADA HOTEL THE ZURI BATURAJA DI KABUPATEN OGAN KOMERING ULU - Krismianto, Putut; Bramana, Sally Maria; Mushoddiq, Achmad Johan (KOLEGIAL, 2024)
The aim to be achieved in this research is to determine the influence of customer experiences on revisitintentions at The Zuri Baturaja Hotel in Ogan Komering Ulu Regency. The method used in this research is adescriptive method, with qualitative and quantitative data analysis techniques. Based on the results of theresearch and discussion that has been carried out, it can be concluded that from the simple linear regressionequation, namely Y= 0.583 + 0.977 . The coefficient of determination or R Square is 0.847 or equal to 84.7%.This shows that Revisit Intention (Y) is influenced by 84.7% by Customer Experience (X) while the remaining15.3% is explained by other factors not explained in this research. The results of the hypothesis test show thatthe tcount of the Customer Experience (X) variable is 13.620. Thus tcount> ttable (23.251>2.03693), thismeans Ho is rejected and Ha is accepted, meaning there is an influence of Customer Experience on GuestRevisit Intention at The Zuri Hotel at The Zuri Baturaja Hotel in Ogan Komering Ulu Regency